2005
DOI: 10.1111/j.1471-4159.2005.03579.x
|View full text |Cite
|
Sign up to set email alerts
|

Cross‐talk of vitamin D and glucocorticoids in hippocampal cells

Abstract: There is growing evidence for a role of vitamin D3 signalling in the brain. In this study, we investigated the influence of vitamin D3, in combination with glucocorticoids, on differentiation of the hippocampal progenitor line HIB5, as well as survival of rat primary hippocampal cells. In HIB5, pre-treatment with dexamethasone (Dex) alone inhibited neurite outgrowth and abolished activation of the mitogen-activated protein kinase (MAPK) pathway during platelet-derived growth factor (PDGF)-induced differentiati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
94
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(97 citation statements)
references
References 50 publications
2
94
0
1
Order By: Relevance
“…Consistent with previous results, 26 Dex decreases neurite outgrowth. Expression of wt FKBP51 abolishes the effect of Dex treatment while K422R mutant fails to prevent it (Figure 3d).…”
Section: Resultssupporting
confidence: 93%
“…Consistent with previous results, 26 Dex decreases neurite outgrowth. Expression of wt FKBP51 abolishes the effect of Dex treatment while K422R mutant fails to prevent it (Figure 3d).…”
Section: Resultssupporting
confidence: 93%
“…This provides a plausible context for interpretation of recently published data linking FLASH to transcriptional activity of the glucocorticoid and mineralocorticoid receptors (15,16). 16306505) from normal epidermal human keratinocytes (American Type Culture Collection, Manassas, VA) RNA were cloned in-frame with the HA tag into pcDNA by using the NheI and XhoI unique restriction sites.…”
Section: Discussionmentioning
confidence: 99%
“…However, this role of FLASH has been questioned (14). More recently it has been shown that, in response to TNF␣, FLASH translocates to the nucleus and binds the glucocorticoid receptor-interacting protein (GRIP-1), inhibiting both its interaction with, and the transcriptional activity of, the glucocorticoid receptor (15,16).…”
mentioning
confidence: 99%
“…Little is known about whether and how disturbing the function of the VDR affects the development of post-traumatic stress disorder, since the regulators of VDR expression in the CNS remains unknown (22). However in vitro evidence indicates that there is cross-talk between the VDR and glucocorticoid receptors in the hippocampus, and that vitamin D is involved in neuronal differentiation and/or apoptosis in this region (23). Mice lacking VDR have exhibited substantial behavioral impairment and increased anxiety (24).…”
Section: Discussionmentioning
confidence: 99%